Pengaruh Lama Perendaman Dingin dan Konsentrasi Ekstrak Limbah Gergajian Kayu Jati terhadap Pengawetan Kayu Pinus melalui Uji Kubur : The Effect of Cold Soaking Duration and Teak Sawdust Waste Extract Concentration on Pine Wood Preservation through Graveyard Test - Desiani, Tutiana Widya; Pertiwi, Yus Andhini Bhekti; Agustina, Ana (HUTAN TROPIKA, 2025)
The low durability class wood usage makes it susceptible to attack by wood-destroying organisms, so preservation is necessary to extend its service life. The present study aimed to determine the effect of teak wood extract concentration, soaking duration, and their interactions on pine wood durability. The preservative used in the present study was teak sawdust waste extract with concentrations of 50 g/L, 100 g/L, and 150 g/L. The cold soaking of teak wood extracts was conducted for 72, 120, and 168 hours. A graveyard test was used to evaluate the durability of wood treated with preservatives. The average absorption of teak extract was 442.4 kg/m3, with the highest absorption obtained in the treatment of 50 g/L teak extract concentration and 168 hours soaking duration (497.3 ± 43.8 kg/m3). Meanwhile, the lowest absorption was obtained in the treatment of 50 g/L teak extract and 72 hours soaking duration (362.8 ± 61.1 kg/m3). The average retention of teak extract was 3.3 kg/m3, with the highest retention in the treatment of teak extract concentration of 150 g/L and 72 hours soaking duration (4.8 ± 1.7 kg/m3) and the lowest in the treatment of teak extract concentration of 150 g/L and 168 hours soaking duration, (1.8 ± 1.2 kg/m3). The results in the present study indicated that the application of teak extract concentration and soaking duration did not significantly affect the absorption and retention of preservatives. The penetration depth of the teak extract was shallow, so changes in the color of the wood in the test sample were only visible on the surface. The highest weight loss was found in the test sample with a teak extract concentration of 150 g/L with 72 hours soaking duration, namely 30.4%. In addition, the lowest weight loss was 2.1% found in the teak extract concentration of 100 g/L with 72 hours soaking duration. There was no interaction between the concentration of teak extract and the difference in soaking duration on wood durability in the graveyard test method. There is a need for diversity in the preservation method given to see if there is an increase in preservatives' absorption, retention, and penetration.